Interest, Concerns, and Attitudes Among Men Who Have Sex With Men and Health Care Providers Toward Prophylactic Use of Doxycycline Against Chlamydia trachomatis Infections and Syphilis. Issue 9 (September 2021) - Park, Justin J.; Stafylis, Chrysovalantis; Pearce, Daniel D.; Taylor, Jeff; Little, Susan J.; Kojima, Noah; Gorin, Aleksandr M.; Klausner, Jeffrey D.
Abstract : A survey-based study found that community members who identify as men who have sex with men and health care providers in Southern California are likely to accept doxycycline preexposure/postexposure prophylaxis to prevent chlamydial infections and syphilis. Supplemental digital content is available in the text. Abstract : Background: Prophylactic administration of doxycycline is regarded as a potential new public health strategy to combat the rising rates of Chlamydia trachomatis infections and syphilis among men who have sex with men. We conducted a survey-based study to evaluate how community members and health care providers in Southern California would perceive doxycycline preexposure/postexposure prophylaxis (PrEP/PEP) to predict its acceptability and identify potential areas of concern. Methods: We conducted an online cross-sectional survey among community members who identify as men who have sex with men and health care providers with prescribing authority in Southern California to investigate the current attitudes toward doxycycline PrEP/PEP, including their willingness to accept. We analyzed the data using descriptive statistics and binary logistic regression. Results: Among 212 enrolled community member participants, 67.5% indicated they would take doxycycline PrEP/PEP if offered by their provider. Higher acceptability was significantly associated with several characteristics, including recent history of bacterial sexually transmitted infection diagnosis and current use of HIV PrEP. For health care providers, 89.5% of 76 enrolled participants expressed willingness to prescribe doxycycline PrEP/PEP to their patients if recommended by the Centers for Disease Control and Prevention, but only 43.4% were willing if not. Both community members and health care providers demonstrated high levels of concern toward possible drug resistance. Conclusions: Doxycycline PrEP/PEP as a preventive strategy against chlamydial infections and syphilis would likely be accepted among community members and health care providers. Clear guidelines from public health officials and further clarification on the strategy's potential impact on developing drug resistance may be necessary to ensure successful implementation.